A philosophical defense of culture perspectives from Confucianism and Cassirer - Xiang, Shuchen (SUNY series in Chinese philosophy and culture., 2021)
Draws on two different but strikingly similar streams in our world tradition to argue for the contemporary philosophical relevance of ""culture.""